If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.5x-0.3(10-3x)=-0.6(x-5)
We simplify the equation to the form, which is simple to understand
0.5x-0.3(10-3x)=-0.6(x-5)
Reorder the terms in parentheses
0.5x+(-3 + 0.9x)=-0.6*(x-5)
Remove unnecessary parentheses
+ 0.5x-3 + 0.9x=-0.6+*(+x-5+)
Reorder the terms in parentheses
0.5x-3 + 0.9x=+(-0.6x+3)
Remove unnecessary parentheses
+ 0.5x-3 + 0.9x=-0.6x+3
We move all terms containing x to the left and all other terms to the right.
+ 0.5x + 0.9x + 0.6x=+3+3
We simplify left and right side of the equation.
+2x=+6
We divide both sides of the equation by 2 to get x.
x=3
| 13=13 | | 1/6x-3=5 | | -7/8v=35 | | 3+y/2=3y/4-2 | | x^2+10x+98=0 | | 6+6x=42+x | | -14-9=12 | | 6(a-7)+20=2(a-7) | | 5(5x-3)+5=-9 | | -22u+-1x= | | 9x-3=6x+39 | | 4-4x=-2x-12 | | 18-3x=-9x | | 3(y+2)=30 | | -4x=-35+3x | | -10-3x=-4x+4 | | -0.2j=-0.2 | | 4+0.16n=3 | | 74=-3+2(-3+2) | | 320=10(x+15)-30 | | -x+31=2x-14 | | 8-2x=-32-6x | | 6y+15=3-2y | | -3(2u-x)-4(x+4u)= | | (x+3)(2x-5)=40 | | -12=(-7)-3.5s | | 2(3x-4)=5(x+7) | | 41=-7x+2(x+8) | | 19+2x=-37+6x | | 6x-21=5(x-3) | | 3/4/5 | | 1/5x=3-1/x |